If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(a + 2) = x + 5 Reorder the terms: F(2 + a) = x + 5 (2 * F + a * F) = x + 5 (2F + aF) = x + 5 Reorder the terms: 2F + aF = 5 + x Solving 2F + aF = 5 + x Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Reorder the terms: -5 + 2F + aF + -1x = 5 + x + -5 + -1x Reorder the terms: -5 + 2F + aF + -1x = 5 + -5 + x + -1x Combine like terms: 5 + -5 = 0 -5 + 2F + aF + -1x = 0 + x + -1x -5 + 2F + aF + -1x = x + -1x Combine like terms: x + -1x = 0 -5 + 2F + aF + -1x = 0 The solution to this equation could not be determined.
| 4-2=14 | | 4.2x+3=11.82 | | 1/3x-3/8=5/8 | | 6a-4=5a-8 | | 6t+4=5t-7 | | 7xy-3y^3+2x-3xy+y^3+10x= | | -2n-(q-1on)= | | 3x-0=1 | | C(-6-c)=0 | | x^2-4x-80=0 | | 3x-26=12 | | 2.2/5=x/4 | | x/2-3/4=(5/8)x+9/4 | | 4.8/7=x/4 | | 2/3=x/4 | | 2.4/5=x/4 | | B(14+b)=0 | | t=25 | | 5.8/7=x/4 | | (4w+3v)(4w-3v)= | | (2x+3)(x-2)=2x | | 5n+3x=n | | 4(x-7)+2=-5(x-2) | | x+3y=n-1 | | 5n+3x= | | 3x-6x=9x | | 16-64=0 | | f(x)=9+1 | | f(x)=-3+1 | | 6(-70%x+6)=5*8-2x | | (3/2)x=15 | | f(x)=-2(3)-5 |